SMEs-Fintech: Support Increase of BMT through financing and recruitment member based of technology - Erwanda Nur Yahya (Review of Islamic Economics and Finance (RIEF), 2018)
This paperto develop online applications to allow users to take advantage of BMT. The method used in this research is qualitative descriptive analysis method in the form of a method to analysis concerned. Writing papers is motivated by fundamental problems that occured in Indonesia, namely poverty. One of the institutions whose role is to alleviate property itself is MFIs (Microfinance Institutions).